Controlled Release of Metformin Loaded Polyvinyl Alcohol (PVA) Microbubble/Nanoparticles Using Microfluidic Device for the Treatment of Type 2 Diabetes Mellitus - SAYIN, FATİH SERDAR; ÇAM, MUHAMMET EMİN; GÜNDÜZ, OĞUZHAN (Springer, 2020)
Nowadays it became obvious that a relentless increase in Type 2 diabetes mellitus (T2DM), affecting the economically affluent countries, is gradually afflicting also the developing world. The currently used drugs in the treatment of T2DM have inefficient glucose control and carry serious side effects. In this study, nano-sized uniform particles were produced by microfluidic method by the explosion of microbubbles. Morphological (SEM), molecular interactions between the components (FT-IR), drug release test by UV spectroscopy measurement were carried out after production process. When microbubbles and nanoparticles, optical microscope and SEM images obtained were examined, it was observed that metformin was successfully loaded into nanoparticles. The diameter of the microbubbles and nanoparticles was 104 ± 91 µm and 116 ± 13 nm, respectively. Metformin was released in a controlled manner at pH 1.2 for 390 min. It is promising in the treatment of T2DM with the controlled release ability of metformin loaded nonoparticles. © Springer Nature Switzerland AG 2020.
Keywords: Diabetes mellitus; Drug delivery; Microbubble; Nanoparticle; T-junction